2016
DOI: 10.1007/s40618-016-0521-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of serum anti-Mullerian hormone (AMH) levels and antral follicle count (AFC) to predict the number of oocytes collected and availability of embryos for cryopreservation in IVF

Abstract: AMH and AFC appear to be valuable markers mainly for ovarian reserve and response to IVF treatment. Serum AMH levels and AFC are significantly associated with the number of retrieved oocytes. Also, a positive correlation with the availability of supernumerary embryos suitable for cryopreservation was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…AMH has been shown to be a strong predictor of ovarian response to exogenous gonadotropins during COH for IVF as well as outcomes such as oocyte yield [18], blastocyst formation [19], blastocyst aneuploidy [20], and surplus embryo cryopreservation at the various stages [2126]. There are conflicting data regarding the ability of AMH to predict clinical pregnancy rates and live birth rates [2731].…”
Section: Discussionmentioning
confidence: 99%
“…AMH has been shown to be a strong predictor of ovarian response to exogenous gonadotropins during COH for IVF as well as outcomes such as oocyte yield [18], blastocyst formation [19], blastocyst aneuploidy [20], and surplus embryo cryopreservation at the various stages [2126]. There are conflicting data regarding the ability of AMH to predict clinical pregnancy rates and live birth rates [2731].…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not investigate the possible association of AMH levels with pregnancy rate. 36 Our study used a short-agonist stimulation protocol, which would be indicated in a population of expected low responders. Counselling these women often proves to be very difficult, since live birth rates are relatively low in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of serum concentrations of AMH have been used along with other measurements, such as for FSH, luteinizing hormone (LH), and E2, for a wide variety of clinical applications. 11 , 22 , 56 , 57 , 58 The clinical use of AMH has advantage over other assays because of its relatively stable level across the menstrual cycle. 50 , 59 , 60 Nevertheless, recent studies have suggested that there is a considerable amount of variation in the level of AMH across cycles in certain women, which implies a risk of misclassification if the variation is beyond 20%.…”
Section: Development Of Amh Assaysmentioning
confidence: 99%